Carbon-Based Quantum Dots for Supercapacitors: Recent Advances and Future Challenges - Fitri Aulia Permatasari; Muhammad Alief Irham; Satria Zulkarnaen Bisri; Ferry Iskandar (Nanomaterials, 2021)
Carbon-based Quantum dots (C-QDs) are carbon-based materials that experience the quantum confinement effect, which results in superior optoelectronic properties. In recent years, C-QDs have attracted attention significantly and have shown great application potential as a high-performance supercapacitor device. C-QDs (either as a bare electrode or composite) give a new way to boost supercapacitor performances in higher specific capacitance, high energy density, and good durability. This review comprehensively summarizes the up-to-date progress in C-QD applications either in a bare condition or as a composite with other materials for supercapacitors. The current state of the three distinct C-QD families used for supercapacitors including carbon quantum dots, carbon dots, and graphene quantum dots is highlighted. Two main properties of C-QDs (structural and electrical properties) are presented and analyzed, with a focus on the contribution to supercapacitor performances. Finally, we discuss and outline the remaining major challenges and future perspectives for this growing field with the hope of stimulating further research progress.